On-line Raman spectroscopy of calcite and malachite during irradiation with swift heavy ions - Dedera, Sebastian; Burchard, Michael; Glasmacher, Ulrich A.; Schöppner, Nicole; Trautmann, Christina; Severin, Daniel; Romanenko, Anton; Hubert, Christian (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2015)
A new on-line Raman System, which was installed at the M3-beamline at the UNILAC, GSI Helmholtzzentrum für Schwerionenforschung Darmstadt was used for first “in situ” spectroscopic measurements. Calcite and malachite samples were irradiated in steps between 1×109 and 1×1012ions/cm2 with Au ions (calcite) and Xe ions (malachite) at an energy of 4.8MeV/u. After irradiation, calcite revealed a new Raman band at 437cm−1 and change of the full width at half maximum for the 1087cm−1 Raman band. The Raman bands of malachite change significantly with increasing fluence. Up to a fluence of 7×1010ions/cm2, all existing bands decrease in intensity. Between 8×1010 and 1×1011ions/cm2 a broad Cu2O band between 110 and 220cm−1 occurs, which superimposes the pre-existing Raman bands. Additionally, a new broad band between 1000 and 1750cm−1 is formed, which is interpreted as a carbon coating. In contrast to the Cu2O band, the carbon band vanished when further irradiating the sample. The installations as well as first in situ measurements at room temperature are presented.